2018
DOI: 10.29333/ejgm/93467
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of biomarker miRNAs signature in colorectal cancer metastasis to liver cancer

Abstract: Introduction: microRNAs (miRNAs) are frequently dysregulated in colorectal cancer (CRC) primary tumors vs. metastasic to the liver. Objective: Our aim was to prediction of biomarker miRNAs signature of CRC Metastasis to liver cancer. Material and Methods: mRNA and miRNA expression profiles of CRC primary tumors to metastases formed in the liver were downloaded from NCBI Gene Expression Omnibus (GEO) database. miRNAs targets were predicted using Targetscan algorithm. The Kyoto Encyclopedia of Genes and Genomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Some studies have accounted for predicted and validated gene targets like GATA2, SKI, NTRK3, PAK2, AR, SP1, and CDK4 that describe their involvement in cancer progression [ 22 ]. It is reported to be upregulated in other cancers like head and neck, breast, cutaneous T-cell lymphoma, and urinary bladder [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have accounted for predicted and validated gene targets like GATA2, SKI, NTRK3, PAK2, AR, SP1, and CDK4 that describe their involvement in cancer progression [ 22 ]. It is reported to be upregulated in other cancers like head and neck, breast, cutaneous T-cell lymphoma, and urinary bladder [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the estrogen level is normal, the vaginal epithelium is wet and thick but estrogen deficiency would develop thin dry layer and for this matter estrogen products are essential to improve such symptoms. However, some studies have shown that hormone therapy in post-menopausal women is accompanied with increased risk of breast cancer, endometrial hyperplasia, thrombosis, and cardiac and cerebral ischemia (Prentice, 2014;Amanlou & Mostafavi, 2017;Salehi, Hadadi, & Tavallaei, 2019;Kilitci, Kaya, Acar, & Elmas, 2018). Hence use of non-estrogen modalities is grown currently.…”
Section: Introductionmentioning
confidence: 99%